A Note on Fuzzy Relation Programming Problems with Max-Strict-t-Norm Composition - Wu, Yan-Kuen; Guu, Sy-Ming (Fuzzy optimization and decision making, 2004)
The fuzzy relation programming problem is a minimization problem with a linear objective function subject to fuzzy relation equations using certain algebraic compositions. Previously, Guu and Wu considered a fuzzy relation programming problem with max-product composition and provided a necessary condition for an optimal solution in terms of the maximum solution derived from the fuzzy relation equations. To be more precise, for an optimal solution, each of its components is either 0 or the corresponding component's value of the maximum solution. In this paper, we extend this useful property for fuzzy relation programming problem with max-strict-<t<-norm composition and present it as a supplemental note of our previous work. [PUBLICATION ABSTRACT]